2014
DOI: 10.1016/j.lwt.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Novel isolates of lactobacilli from fermented Portuguese olive as potential probiotics

Abstract: The purpose of this work was to screen for and characterize the potential probiotic features of strains of lactic acid bacteria isolated from Galega cultivar fermented olives, to eventually develop an improved probiotic food from plant origin. From 156 isolated strains, 10 were acid e and bile salt tolerant, and exhibited survival rates up to 48%, following simulated digestion. All strains exhibited auto-(4-12%) and co-aggregation features (≥30%), as well as hydrophobicity (5-20%) and exopolysaccharide-produci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 88 publications
8
62
0
2
Order By: Relevance
“…Several studies showed that the percentage of LAB adhesion to gastric cells and Caco-2 cells is strain-dependent (Pisano et al, 2014;Delgado et al, 2015). However, Peres et al (2014) showed that the adhesion of Lactobacillus plantarum (LB95) and Lactobacillus paraplantarum (LB13) strains to Caco-2 cells was not significantly different from that of Lactobacillus casei Shirota, which is consistent with our results pertaining to HT-29 cells.…”
Section: Adhesion and Invasion Ability Of Strains To Ht-29 Cellssupporting
confidence: 92%
See 3 more Smart Citations
“…Several studies showed that the percentage of LAB adhesion to gastric cells and Caco-2 cells is strain-dependent (Pisano et al, 2014;Delgado et al, 2015). However, Peres et al (2014) showed that the adhesion of Lactobacillus plantarum (LB95) and Lactobacillus paraplantarum (LB13) strains to Caco-2 cells was not significantly different from that of Lactobacillus casei Shirota, which is consistent with our results pertaining to HT-29 cells.…”
Section: Adhesion and Invasion Ability Of Strains To Ht-29 Cellssupporting
confidence: 92%
“…The two probiotics used as reference LABs were Lactobacillus casei Shirota (ACA-DC 6002) and Lactobacillus rhamnosus GG, provided by the Laboratory of Microbiology and Biotechnology of Food at the Agricultural University of Athens (Iera Odos, Greece). The two selected LABs used in this study, Lactobacillus plantarum (LB95) and Lactobacillus paraplantarum (LB13), came from industrial and homemade fermented olives of Portuguese cultivars (Peres et al, 2014), and were made available by Instituto de Tecnologia Química e Bioló gica, New University of Lisbon (Oeiras, Portugal). The pathogenic strains used were: Listeria monocytogenes EGDe, originally obtained from Institut National de la Recherche Agronomique (Tours, France), E. coli O157 : H7 (ATCC 43895), E. coli B from Coleção de Bactérias do Instituto Superior de Agronomia, University of Lisbon (Lisbon, Portugal), and S. Typhimurium (ATCC 14028) and S. Enteritidis from Instituto de Ciência Aplicada e Tecnologia, University of Lisbon (Lisbon, Portugal).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased awareness of food functionality has paralleled consumers' trend of whole life care; consumers recognize that food can bring about health benefits, owing to their influence upon colonic microbiota, via phytochemical and phenolic components; they can co-exist with western medical approaches to disease (Furtado-Martins et al, 2013), either by promoting growth of beneficial microorganisms or acting against pathogens (Peres et al, 2014;Peres, Hernandez-Mendonza, Peres, & Malcata, 2013). Table olives are important components of the Mediterranean diet, which has been associated to numerous health benefits arising from the presence of such compounds as organic acids, pigments and phenolics known to exhibit multiple biological activities (Rahele, Farooq, Khalid, Anwarul-Hassan, & Nazamid, 2012).…”
Section: Introductionmentioning
confidence: 99%